2015
DOI: 10.2196/jmir.4207
|View full text |Cite
|
Sign up to set email alerts
|

e-CBT (myCompass), Antidepressant Medication, and Face-to-Face Psychological Treatment for Depression in Australia: A Cost-Effectiveness Comparison

Abstract: BackgroundThe economic cost of depression is becoming an ever more important determinant for health policy and decision makers. Internet-based interventions with and without therapist support have been found to be effective options for the treatment of mild to moderate depression. With increasing demands on health resources and shortages of mental health care professionals, the integration of cost-effective treatment options such as Internet-based programs into primary health care could increase efficiency in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 66 publications
1
58
0
1
Order By: Relevance
“…Because all forms of CCBT use less therapeutic support than conventional psychotherapy, it is has been assumed that CCBT is a cost-effective strategy [10,19,34,35]. However, only a small number of earlier studies included the components necessary to assess cost-effectiveness in comparison to standard, first-line interven- tions (i.e., randomization to a credible, active comparison group and a detailed assessment of service utilization, costs, and lost economic potential) [36][37][38][39][40][41]. Keeping in mind these limitations, results of a meta-analysis of the earlier RCTs suggested that CCBT may be more cost-effective than standard CBT [42].…”
Section: Discussionmentioning
confidence: 99%
“…Because all forms of CCBT use less therapeutic support than conventional psychotherapy, it is has been assumed that CCBT is a cost-effective strategy [10,19,34,35]. However, only a small number of earlier studies included the components necessary to assess cost-effectiveness in comparison to standard, first-line interven- tions (i.e., randomization to a credible, active comparison group and a detailed assessment of service utilization, costs, and lost economic potential) [36][37][38][39][40][41]. Keeping in mind these limitations, results of a meta-analysis of the earlier RCTs suggested that CCBT may be more cost-effective than standard CBT [42].…”
Section: Discussionmentioning
confidence: 99%
“…Internet-delivered (eHealth) prevention programs can provide a cost-effective alternative to traditional approaches, by enabling wider dissemination and scalability of effective preventative strategies [ 4 ]. Encouragingly, a recent meta-analysis found that eHealth prevention interventions had small positive effects on symptom reduction for depression and anxiety, with similar findings for both universal and selective/indicated prevention interventions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of Internet-delivered interventions offers a potential solution to mitigate these impacts [ 13 - 15 ]. myCompass is a broadly available and efficacious public health intervention that can be delivered at minimal cost [ 45 ]. It therefore presents itself as a potentially effective and timely option for reducing unmet mental health need and ameliorating the personal and societal impact of co-occurring depression and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%